Scientometric analysis in e-leadership and competencies for its development - Molina-Moran, Ronny; Castañeda-Betancur, Santiago; Ardila-Niño, Gustavo; Villao-Santos, Freddy (Clío América, 2024)
The aftermath of the COVID-19 pandemic has witnessed an exponential surge in the literature on e-leadership, establishing it as a prominent research topic in both industrial and academic organizations. However, the existing literature remains disparate, with a conspicuous absence of studies that connect cohesively the principal contributions with the current subareas. This investigation's primary objective is to delineate the evolution of e-leadership and its connection with competencies and provide an overarching view from a scientometric standpoint. The methodology employed is divided into two sections: the initial section elucidates the annual scientific production, country-specific contributions, journal publications, and author collaboration analysis. Subsequently, researchers deploy the Tree of Science algorithm to discern the roots, trunk, and branches of e-leadership; findings reveal a remarkable growth trajectory since 2020, with three primary subareas emerging: e-leadership in the educational context, virtual teams competencies, and innovation leadership. The implications of this study are instrumental for managers, aiding them in identifying the pivotal skills requisite in this burgeoning digital era.